Global analysis of the TRAPPIST Ultra-Cool Dwarf Transit Survey. Issue 3 (15th July 2020) - Lienhard, F; Queloz, D; Gillon, M; Burdanov, A; Delrez, L; Ducrot, E; Handley, W; Jehin, E; Murray, C A; Triaud, A H M J; Gillen, E; Mortier, A; et al.
ABSTRACT: We conducted a global analysis of the TRAPPIST Ultra-Cool Dwarf Transit Survey – a prototype of the SPECULOOS transit search conducted with the TRAPPIST-South robotic telescope in Chile from 2011 to 2017 – to estimate the occurrence rate of close-in planets such as TRAPPIST-1b orbiting ultra-cool dwarfs. For this purpose, the photometric data of 40 nearby ultra-cool dwarfs were reanalysed in a self-consistent and fully automated manner starting from the raw images. The pipeline developed specifically for this task generates differential light curves, removes non-planetary photometric features and stellar variability, and searches for transits. It identifies the transits of TRAPPIST-1b and TRAPPIST-1c without any human intervention. To test the pipeline and the potential output of similar surveys, we injected planetary transits into the light curves on a star-by-star basis and tested whether the pipeline is able to detect them. The achieved photometric precision enables us to identify Earth-sized planets orbiting ultra-cool dwarfs as validated by the injection tests. Our planet-injection simulation further suggests a lower limit of 10 per cent on the occurrence rate of planets similar to TRAPPIST-1b with a radius between 1 and 1.3 R⊕ and the orbital period between 1.4 and 1.8 d.